Gonadotropins as novel active partners in vascular diseases: Insight from angiogenic properties and thrombotic potential of endothelial colony‐forming cells. (29th October 2021) - Détriché, Grégoire; Gendron, Nicolas; Philippe, Aurélien; Gruest, Maxime; Billoir, Paul; Rossi, Elisa; Guerin, Coralie L.; Lokajczyk, Anna; Brabant, Séverine; Prié, Dominique; Mirault, Tristan; Smadja, David M.
Abstract: Background: The impact of estrogen and testosterone on atherosclerotic cardiovascular disease is well known, but the role of the gonadotropins follicle‐stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL) to some extent remain less studied. Objectives: To explore the angiogenic potential of gonadotropins on endothelial colony‐forming cells (ECFCs). Methods: We examined the effects of various doses of gonadotropins on ECFCs obtained from cord blood by assessing colony number, proliferation, migration, and sprouting ability. Moreover, we studied thrombin generation in ECFCs exposed to gonadotropins by performing a thrombin generation assay. Finally, we determined the levels of circulating gonadotropins in 30 men, to exclude the effect of estrogen, with lower extremity arterial disease (LEAD), in comparison with age‐ and sex‐matched controls. Results: Exposure to FSH, LH, or PRL resulted in an increase in ECFC migration but showed no effect on proliferation or ECFC commitment from cord blood mononuclear cells. Using a three‐dimensional fibrin gel assay, we showed that ECFC sprouting was significantly enhanced by gonadotropins. Exposure to FSH also increased the thrombin generation of ECFCs exposed to FSH. Finally, FSH and LH levels in men with LEAD were higher than those in controls. Conclusion: Gonadotropins increase ECFC‐related angiogenesis and may be involved in thrombin generation in cardiovascular disease. Gonadotropins may act as biomarkers; moreover, we hypothesize that gonadotropin‐blocking strategies may be a novel interesting therapeutic approach in atherosclerotic cardiovascular disease.